Relationship between insulin resistance and dietary intake of vitamins D and E in women with PCOS based on Rotterdam criteria - Maryam Movahedinejad; Saeideh Ziaei; Anoushirvan Kazemnejad; Zahra Kamali (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2021)
Introduction: Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder with oxidative stress in women of reproductive age. Oxidative stress is an important factor in the development of insulin resistance. Some nutrients are linked to oxidative stress. This study was performed with aim to determine the relationship between insulin resistance and dietary intake of vitamins D and E in PCOS subgroups.Methods: This case-control study was performed in 2015-2016 on 151 women with PCOS who were divided into four groups according to Rotterdam diagnostic criteria (D (H+O) = 37, C (P+O) = 40, B (H+P)= 33, A (H+P+O) = 41 and 31 women in the control group). Daily intake of vitamin D and vitamin E was assessed using a 168 items PPQ food frequency questionnaire. Insulin resistance was diagnosed with HOMA index (Cut off> 2.5). Data were analyzed by SPSS software (version 22) and Kruskal-Wallis, one-way ANOVA, Chi-square and Spearman tests. P<0.05 was considered statistically significant.Results: In the subgroups of A, D and control group, a significant negative relationship was observed between HOMA insulin resistance index with vitamin D (P = 0.022), (P = 0.049) and (P = 0.025), respectively and with vitamin E (P = 0.036), (P = 0.001) and (P = 0.001), respectively. In the subgroups of B and C, no relationship between HOMA insulin resistance index with vitamin D and vitamin E (P> 0.05).Conclusion: Due to the relationship between insulin resistance and vitamins D and E in PCOS subtypes, it is recommended to increase the intake of vitamins D and E to improve health parameters in PCOS subjects.